Isolation and structure elucidation of pectic polysaccharide from rose hip fruits (Rosa canina L.). (20th October 2016) - Ognyanov, Manol; Remoroza, Connie; Schols, Henk A.; Georgiev, Yordan; Kratchanova, Maria; Kratchanov, Christo
Highlights: Pectin is extracted from rose hip fruits by citric acid. Yield, molecular weight, and chemical composition of the pectin are evaluated. Rose hip pectin is mainly built up by homogalacturonan segments. Different blocks of ester distributions are present within the rose hip pectin. Abstract: A pectic polysaccharide from rose hip (RH) fruits has been obtained by extraction with 1% aqueous citric acid. It was found that the polysaccharide fraction mainly consisted of galacturonic acid (45.5%) next to galactose (5.5%) and arabinose (4.7%). RH pectin is having a relatively high degree of methylesterification (62%) and acetylation (10%) and consists of different molecular weight populations in the range of 10–100 kDa. Enzymatic fingerprinting was performed using a combination of pectin lyase (PL) and endo -polygalacturonase. Detailed information about the structure and level of galacturonic acid oligomers released was obtained using LC-HILIC-MS/ELSD and HPAEC. Predominantly, unsaturated and methyl-esterified oligomers (DP 3–5) were released indicating that high proportions of methylesterified 'PL degradable' areas were present within the pectin. The data revealed that homogalacturonan is the main building block of the extracted pectin and consists of long methylesterified/acetylated GalA sequences interspersed with small blocks of non-methyl-esterified GalA units.